A comparative analysis of two point cloud volume calculation methods. Issue 8 (18th April 2019) - Li, Bin; Wei, Junbo; Wang, Lu; Ma, Bochao; Xu, Mingxia
ABSTRACT: A spatial body object morphology analysis basically consists of the volume parameter. However, the challenge lies in the volume calculations of irregular objects. A point cloud slicing method (PCSl ) is proposed in this study. In this method, a uniformly spaced sequential slicing process is first conducted in a specific direction through the point cloud of a spatial object obtained via three-dimensional laser scanning (3DLS). A series of discrete point cloud slices corresponding to the point cloud body are then obtained. Subsequently, the outline boundary polygons of the point cloud slices are searched one by one in accordance with the slicing sequence and the areas of the polygons. The point cloud slice is also calculated. Finally, the individual point cloud section volume is calculated throughout the slicing areas and the adjacent slicing gap. In this way, the total volume of the scanned spatial object can be calculated by summing up the individual volumes. According to the results and analyses of the calculated examples, the slice-based volume-calculating method for the point cloud of irregular objects obtained via 3DLS is correct and has a concise process, reliable results, efficient calculation methods and a controllable accuracy. The PCSl algorithm proposed in this study effectively works to overcome the disadvantages of the point cloud segmenting method. It also provides a quick and accurate solution to the volume calculation of a point cloud of a spatial object obtained via 3DLS. This method provides a good solution for volume calculations of irregular objects.